Relative abundance of a mesocarnivore in a human-dominated, semi-arid rangeland in Namibia - Reasoner, Emma; Marker, Laurie; Verschueren, Stijn; Briers-Louw, Willem D.; Mbidzo, Meed; Cristescu, Bogdan (Frontiers in Ecology and Evolution, 2024)
Mesocarnivores fill important roles in ecological communities globally, but their distribution and abundance are often understudied. Many species have historically been regarded as vermin and subject to lethal control due to their role in livestock predation. Identifying the factors influencing mesocarnivore populations can help disentangle their relationship within ecological communities and inform conflict mitigation and conservation priorities. To help identify these factors, we used camera traps to study the community of medium and large mammals in four communal conservancies of northeastern Namibia covering the wet and dry seasons using 99 and 97 camera trap stations, respectively. We modelled black-backed jackal (Lupulella mesomelas) abundance using the robust Royle-Nichols model. Black-backed jackal were widespread, with a mean per site abundance of 2.01 (SD=0.66) in the wet season and 2.41 (SD=0.49) in the dry season. Black-backed jackal showed seasonally contrasting covariate associations, with lower abundance in areas with medium and large-sized wild prey during the wet season, and higher abundance in areas with more villages and close to African wild dog (Lycaon pictus) dens in the dry season. We identified localized hotspots of black-backed jackal abundance during the dry season, which may indicate that when resources are scarce, black-backed jackals rely on anthropogenic food sources despite an elevated risk for conflict, and on carcass remains from African wild dog kills. These findings highlight potential drivers of mesocarnivore abundance that would be obscured in a conventional occurrence modelling framework, and illustrate how local abundance may be influenced by seasonal variability, wild and anthropogenic food sources, and a likely facilitative relationship with a large carnivore. Further investigations in areas with more complex carnivore guilds and higher density of dominant predators are needed to understand black-backed jackal-African wild dog interactions and impacts on population dynamics.